Carlos Cañola “Martinete”, un mediador político y cultural en el Medellín de mediados del siglo XX (2013)
ABSTRACT: Between 1938 and 1965 the urban population of Medellín (Antioquia) experienced the idea of “civic centers”, institutional neighborhood sociability structure and policy that tried to approach the municipal administration. Around relations between residents and the mayor emphasized Carlos Cañola “Martinete” a character who known to unite neighborhood efforts, the implementation of the values from the elite groups and implementation of public policies on civic discourse - religious ruling at the time. This article aims to analyze the forms of political and cultural mediation directly served as a bridge between civil society and state in this Colombian city.